Deletion of genes linked to the C1-fixing gene cluster affects growth, by-products, and proteome of Clostridium autoethanogenum - Nwaokorie, Ugochi Jennifer; Reinmets, Kristina; de Lima, Lorena Azevedo; Pawar, Pratik Rajendra; Shaikh, Kurshedaktar Majibullah; Harris, Audrey; Köpke, Michael; Valgepea, Kaspar (Frontiers in Bioengineering and Biotechnology, 2023)
Gas fermentation has emerged as a sustainable route to produce fuels and chemicals by recycling inexpensive one-carbon (C1) feedstocks from gaseous and solid waste using gas-fermenting microbes. Currently, acetogens that utilise the Wood-Ljungdahl pathway to convert carbon oxides (CO and CO2) into valuable products are the most advanced biocatalysts for gas fermentation. However, our understanding of the functionalities of the genes involved in the C1-fixing gene cluster and its closely-linked genes is incomplete. Here, we investigate the role of two genes with unclear functions – hypothetical protein (hp; LABRINI_07945) and CooT nickel binding protein (nbp; LABRINI_07950) – directly adjacent and expressed at similar levels to the C1-fixing gene cluster in the gas-fermenting model-acetogen Clostridium autoethanogenum. Targeted deletion of either the hp or nbp gene using CRISPR/nCas9, and phenotypic characterisation in heterotrophic and autotrophic batch and autotrophic bioreactor continuous cultures revealed significant growth defects and altered by-product profiles for both ∆hp and ∆nbp strains. Variable effects of gene deletion on autotrophic batch growth on rich or minimal media suggest that both genes affect the utilisation of complex nutrients. Autotrophic chemostat cultures showed lower acetate and ethanol production rates and higher carbon flux to CO2 and biomass for both deletion strains. Additionally, proteome analysis revealed that disruption of either gene affects the expression of proteins of the C1-fixing gene cluster and ethanol synthesis pathways. Our work contributes to a better understanding of genotype-phenotype relationships in acetogens and offers engineering targets to improve carbon fixation efficiency in gas fermentation.